CONTEXTUAL DESIGN: PENDEKATAN KEARIFAN LOKAL DALAM KONSEP PERANCANGAN DIGITAL START-UP VALLEY PIYUNGAN, YOGYAKARTA - Ahmad Ibrahim Rahmani (Indonesian Society of Applied Science, 2023)
This article discusses how the contextual approach of local wisdom values can be considered in determining project design concepts. In this case the concept of digital start-up valley Piyungan applies the contextual division of zones into 3 parts that follow the pattern of the existing space in the location, namely the Education Zone, namely the public zone for Campus IT education. The second zone is a digital park area which is bounded by natural tributaries on a maintained site to give a recreational impression. And the third zone which is in the most private area is designated as the digital office area as the digital start-up valley office location. This article is the result of an exploration of design concepts that produce a conceptual approach that is also embodied in applying the concept of campus digital modern learning activities which are accommodated in traditional building concepts that adopt local wisdom principles from the local culture Artikel ini membahas bagaimana pendekatan kontekstual dari nilai-nilai kearifan lokal dapat dipertimbangkan dalam menetukan konsep perancangan proyek. Dalam hal ini konsep digital start-up valley Piyungan mengaplikasikan kontekstual pembagian zona dalam 3 bagian yang mengikuti pola ruang eksisting yang telah ada dilokasi yaitu Zona edukasi yakni zona publik untuk pendidikan IT Campus. Zona kedua berupa area digital park yang dibatasi oleh anak sungai alami pada tapak yang dipertahankan untuk memberi kesan rekreatif. Dan zona ketiga yang berada pada area paling privat diperuntukan sebagai area digital office sebagai lokasi perkantoran digital start-up valley. Artikel ini merupakan hasil eksplorasi konsep desain yang menghasilkan pendekatan konseptual juga diwujudkan dalam mengaplikasikan konsep kegiatan pembelajaran modern digital kampus yang diakomodasi dalam konsep bangunan tradisional yang mengadopsi prinsip-prinsip kearifal lokal dari budaya setempat..